1988
DOI: 10.1017/s0021859600083179
|View full text |Cite
|
Sign up to set email alerts
|

The response of field beans (Vicia faba L.) to irrigation and sowing date:1. Yield and yield components

Abstract: The response of 4 crops of autumn-and spring-sown field beans cv. Maris Bead to irrigation applied during the vegetative, flowering and pod-filling phases was examined during 1981-2 and 1982-3. The crops, grown on a Templeton silt-loam, were irrigated weekly in amounts equal to the difference between the estimated evapotranspiration and rainfall of the previous week using trickle irrigation.Seed yield of fully irrigated autumn-and spring-sown crops (averaged over the two seasons), was 5-2 and 3-3 t/ha respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
5
18
1
Order By: Relevance
“…These results make suppose a difficult adaptation of lupin Luxe to soil and climatic condition of Mugello area, irrespective of sowing times, as shown in Table 4. Field bean shown a higher value of plant's height in autumnal sowing, respect to late winter sowing, in agreement with results obtained by other authors (Husain et al, 1988;Duzdemir and Ece, 2011). In the case of pea and lupin species, there is no effect on plant's height in relation to sowing season.…”
Section: Discussionsupporting
confidence: 91%
“…These results make suppose a difficult adaptation of lupin Luxe to soil and climatic condition of Mugello area, irrespective of sowing times, as shown in Table 4. Field bean shown a higher value of plant's height in autumnal sowing, respect to late winter sowing, in agreement with results obtained by other authors (Husain et al, 1988;Duzdemir and Ece, 2011). In the case of pea and lupin species, there is no effect on plant's height in relation to sowing season.…”
Section: Discussionsupporting
confidence: 91%
“…Although Coyne (1965) was not successful with selection for yield or for yield components in common bean, Sarafi (1978) showed that selection was effective in increasing the number of pods/plant with no simultaneous change in the levels of the other yield components and Coyne (1968) recommended this trait for selection for yields. The 'components of yield' approach has been used widely to explain variations in the yield of grain legumes such as peas (Pisum sativum L.) (Nichols et al 1985), field bean (Vicia faba L.) (Husain et al 1988) and Phaseolus vulgaris (Dapaah et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports of seed yield increases with irrigation of P. vulgaris (Martin 1982;Love et al 1988). In Canterbury, White et al (1982) and Husain et al (1988a) reported similar results for peas and field beans. The increase in seed yield resulted from more pods per plant, more seeds per pod and a greater 100 seed weight.…”
Section: Seed Yield and Harvest Indexmentioning
confidence: 56%
“…27 Two factors which exert a large influence on the yield of grain legumes in Canterbury are sowing date and irrigation (Wilson 1987;Husain et al 1988a;McKenzie & Hill 1990). Timely seeding has long been recognised as a key to efficient crop production.…”
mentioning
confidence: 99%